Social Policy in the Curriculum Formation of Brazilian Social Work - Wellen, Henrique; Rodrigues, Raída Venceslau de Oliveira; Silva, Ozileia Cardoso da (Argumentum, 2024)
The objective was to analyse central expressions of the different approaches to social policies within the academic literature used in undergraduate courses in Social Work in Brazil. Therefore, we sought to identify and characterize the main theoretical references on social policies that are present in the curriculum of these courses, based on a documental analysis. The results are presented based on the apprehension of three central aspects: the predominance of the discussion of social policies in curricular periods; the relationship between training in social policies and formation nucleus (from ABEPSS); and the most used bibliographical references in social policy curriculum components more present in undergraduate courses.